2002
DOI: 10.1046/j.1365-2036.2002.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Cisapride inhibits meal‐stimulated gastric acid secretion and post‐prandial gastric acidity in subjects with gastro‐oesophageal reflux disease

Abstract: Summary Background and aims : KCNQ1 potassium channels in human gastric parietal cells are thought to be involved in gastric acid secretion. As cisapride can inhibit similar channels in other tissues and is an effective treatment for nocturnal heartburn, we examined the effects of cisapride on gastric and oesophageal acidity, gastric emptying and heartburn severity in subjects with gastro‐oesophageal reflux disease. Methods : Subjects (n=11) had suffered from heartburn four times or more per week for at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…However, treatment with prokinetic agents has been shown to improve several symptoms in patients with GERD (16,39), and we have recently demonstrated that cisapride improves the motility proximal to the lower esophageal sphincter in GERD rats (40). These findings suggest that gastrointestinal dysmotility is involved in GERD progression.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, treatment with prokinetic agents has been shown to improve several symptoms in patients with GERD (16,39), and we have recently demonstrated that cisapride improves the motility proximal to the lower esophageal sphincter in GERD rats (40). These findings suggest that gastrointestinal dysmotility is involved in GERD progression.…”
Section: Discussionmentioning
confidence: 66%
“…Delayed gastric emptying occurs frequently among patients with acid reflux (3,31), and treatment with prokinetic agents, which are agonists of the 5-hydroxytryptamine 4 (5-HT 4 ) receptor, partially improves symptoms in patients with GERD (16,39). Thus it was concluded that gastric dysmotility is also a factor involved in acid reflux into the esophagus (3,10,29,31).…”
mentioning
confidence: 99%
“…Published evidence suggests that oral cisapride does not modify postprandial LOS motor function [25,26], although an overnight study showed a decrease in the rate of transient LOS relaxations [27]. It cannot be excluded therefore that cisapride decreased the number of acid (pH B/4) reflux episodes only, instead of the total number of reflux episodes through its decreasing effect on mealstimulated gastric acid secretion [28], a hypothesis that needs to be tested by combined intra-oesophageal pH and impedance monitoring.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, we developed a technique to measure meal‐stimulated gastric acid secretion based on the buffer capacity of the meal determined in vitro and the time required for the gastric pH to decrease to pH 2 in vivo following ingestion of the meal 16 ,. 17 These studies, however, involved a single meal ingested by subjects who were restricted to a bed or a chair in a study unit 16 ,. 17 …”
Section: Introductionmentioning
confidence: 99%
“… 17 These studies, however, involved a single meal ingested by subjects who were restricted to a bed or a chair in a study unit 16 ,. 17 …”
Section: Introductionmentioning
confidence: 99%